2021
DOI: 10.5937/etp2101042a
|View full text |Cite
|
Sign up to set email alerts
|

The crisis answer system of the flood economic damage decrease

Abstract: In this paper the role and importance basic problems of the crisis answer system of the flood economic damage decrease are considered. The phases of that system and estimate procedure of flood risk are defined, by using scientific methods analysis, synthesis and description. The basic aspects of the economic damage posible decrease are analysed, by using the case study example. The main importace of the flood prevention is emphasized, as a proposal for the crisis management practice. The investment importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…An active lifestyle accomplishes positive changes in muscle functioning. When the muscle system works, fat burns easily and more efficiently (Wargo and Kurath, 2012), and for these reasons, it is necessary to choose an adequate recreational program that can proficiently contribute to obesity reduction, if not its elimination, and act preventively against locomotor apparatus disease and the cardiovascular and nerve system (Aćimović and Špirtović, 2012;Wargo and Kurath, 2012). Numerous studies have confirmed a positive effect of different aerobic programs on the changes in body composition and anthropometric characteristics of a man (Osei-Tutu and Campagna, 2005;Rahimi, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An active lifestyle accomplishes positive changes in muscle functioning. When the muscle system works, fat burns easily and more efficiently (Wargo and Kurath, 2012), and for these reasons, it is necessary to choose an adequate recreational program that can proficiently contribute to obesity reduction, if not its elimination, and act preventively against locomotor apparatus disease and the cardiovascular and nerve system (Aćimović and Špirtović, 2012;Wargo and Kurath, 2012). Numerous studies have confirmed a positive effect of different aerobic programs on the changes in body composition and anthropometric characteristics of a man (Osei-Tutu and Campagna, 2005;Rahimi, 2006).…”
Section: Introductionmentioning
confidence: 99%